Characteristics Of Chronic Supurative Otitis Media: Literature Review - Rahmi Hidayanti Pelu; Sri Wartati; Sidrah Darma (Jurnal EduHealth, 2024)
Introduction:Chronic suppurative otitis media (OMSK) was previously called otitis media perforata (OMP) or colloquially known as congek. What is called chronic suppurative otitis media is a chronic infection in the middle ear with perforation of the tympanic membrane and secretions coming out of the middle ear continuously or intermittently.Objective:This literature aims to look at the picture of chronic suppurative otitis media. Method: This research uses a literature review method. Scientific articles or journals are downloaded from PubMed, Garuda Portal, and Google Scholar with SINTA IV and V standards in the 2015-2023 period. The keywords in the search for this article are characteristics, chronic supportive otitis media. Results: In this literature, there were 6 research articles that reported the description of chronic suppurative otitis media. Conclusion:The description of chronic suppurative otitis media based on gender is more common in men than women, CSOM patients based on type have more benign types than malignant types, in CSOM patients based on the main complaint there are more otorrhea than hearing loss and otalgia.